Dual-drainage pulmonary venous return of the left upper lobe - Yeka W. Nmadu; Robert F. English (Wolters Kluwer Medknow Publications, 2024)
Dual drainage of a pulmonary vein is an unusual anomaly of pulmonary venous drainage. While being evaluated for hypertension, a child was found with dual drainage of the upper left lobe through a vertical vein that connects to the normal pulmonary vein as well as the innominate vein with no symptoms from his effective left-to-right shunt.